(untitled) (Palíndromo, 2013)
In this paper is intended to show some doubts that remained in the end of the dissertation “As Tramas dos Tapeceiros Narradores: Técnica e Criação” and some topics signed by counseling at the time. In the last four years, reading and amplifying my bibliographical repertory, new approaches appeared to discuss these questions and mostly to map a possible research construction. This study aims to analyze a set of tapestries’ images from different periods of history altogether, along to paintings or drawings and the cards that originated them. It implicates still perceiving this sequence of activities and thus be able to analyze if the card brings the painting’s memory, and on the other hand if tapestry has its own potential so this work can become the happening. Initially the set of images that will serve as reference to analyze the other contemporary tapestries is a series produced between 1370/80 named “The Apocalypse”. The other series of tapestries, produced from drawings of the French artist Jean Lurçat, in the mid-twentieth century, named Le Chant Du Monde will also be an important referential. In Brazil the study will serch the tapestries made from the landscaper paintings’ Roberto Burle Marx. The contemporary tapestry weavers Archie Brennan, Sarah Swett and Jean Pierre Larochette were chose by the relevance of their works, different backgrounds and production processes. The way they relate to contemporary art events and which are the worries towards the tapestry’s production in the contemporary.